2013
DOI: 10.2460/javma.242.3.366
|View full text |Cite
|
Sign up to set email alerts
|

Use of the vertebral heart scale for differentiation of cardiac and noncardiac causes of respiratory distress in cats: 67 cases (2002–2003)

Abstract: Results suggested that the VHS system may be a useful tool to help differentiate cardiac from noncardiac causes of respiratory distress in cats in an emergency situation when an echocardiogram is not available or is not plausible in an unstable patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 28 publications
3
30
0
Order By: Relevance
“…The utility of thoracic radiographs in distinguishing hydrostatic pulmonary edema from high‐permeability pulmonary edema has been evaluated in several studies, and the accuracy of this imaging modality is variable. This is especially true in cats, as they commonly display high variability in radiographic signs of congestive heart failure . Echocardiography is currently the gold standard to rule out hydrostatic pulmonary edema in veterinary medicine.…”
Section: Discussionmentioning
confidence: 99%
“…The utility of thoracic radiographs in distinguishing hydrostatic pulmonary edema from high‐permeability pulmonary edema has been evaluated in several studies, and the accuracy of this imaging modality is variable. This is especially true in cats, as they commonly display high variability in radiographic signs of congestive heart failure . Echocardiography is currently the gold standard to rule out hydrostatic pulmonary edema in veterinary medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiomyopathy might be suspected when severe cardiomegaly is present radiographically, when a left auricular bulge is present on dorsoventral/ventrodorsal radiographic views, or both . Thoracic radiography is insensitive for identification of mild or moderate cardiac changes associated with cardiomyopathy, and in some cats the cardiac silhouette may appear normal even when disease is severe enough to cause CHF .…”
Section: Diagnosismentioning
confidence: 99%
“…32 However, in cats with incidentally detected murmurs (where clinical signs are absent by definition), a higher rate of false-negative results could be expected than for cats with signs referable to the cardiovascular system. Measurement of circulating NT-proBNP concentration also has value for detection of occult cardiomyopathy; in 1 study, 33 a result < 50 pmol/L indicated cardiomyopathy was very unlikely, whereas a result > 100 pmol/L suggested cardiomyopathy was present.Thoracic radiography, NT-proBNP testing, or both may be useful when client limitations (financial, logistic, geographic, or other) prevent the cat from undergoing complete 2-D and Doppler echocardiography ( Figure 6).…”
Section: Heart Murmurs In Adult and Geriatric Catsmentioning
confidence: 99%